Is the Family Health Center Professionals’ Knowledge Level About Child Abuse and Neglect Sufficent? A Comprehensive Field Study - Deniz, Serdar; Bayraktar, Muhammet; Nayir, Tufan; Balcı, Elçin; İnceoğlu, Feyza (Children (Basel), 2025)
Background: Child abuse and neglect bring lots of undesirable consequences for the future of children and societies with it. It is expected that health service providers have sufficient knowledge about that subject in order to determine abuse and neglect. Materials and methods: In this study, a 67-item scale with a Cronbach’s alpha value of 0.92 was used. A score of more than 3 on the scale meant that the score was at a sufficient level. The universe of this descriptive study is health professionals working in 512 family health units in Mersin, Türkiye. Interviews were conducted with 97.26% (n = 249) of family physicians and 98.04% (n = 251) of family health workers working in the 256 units included in the sample. Results: Since the overall scale score of the study group was above 3, it (3.77 ± 0.36) was determined that the average score of the participants was sufficient. 46.2% (n = 231) of the group did not receive training on child neglect and abuse during their education, and 45.2% (n = 226) during their work. 95.8% stated that they paid attention to signs of abuse and neglect in children brought for examination and follow-up, while 83.4% stated that they had not encountered any cases in the last year. 42% (n = 210) of the group thought that the relevant authorities would not take the necessary action even if they observed signs of child neglect and abuse, while 37.4% (n = 187) stated that they did not know when and how to report. Conclusions: Although the findings of the study suggest that the group’s level of knowledge is sufficient, it is of great importance to increase their knowledge about reporting processes and to encourage them in this regard.